Formulation and antimicrobial activity evaluation of a 0.2% chlorhexidine canine mouthwash with essential oils - González Corrales, Daniela (2021)
Background: Periodontal disease is the infection and inflammation of the gums, bones, and tissues involved in teeth support, and it is one of the most common diseases affecting pet dogs. Essential oils have shown antimicrobial activity against bacteria causing periodontal disease; therefore, they are considered potential therapeutic agents. Objectives: The main objective was to formulate and evaluate the antimicrobial activity of a 0.2% chlorhexidine canine mouthwash with essential oils. Methods: Three microemulsion formulations were obtained by constructing a pseudo-ternary phase diagram using the phase titration method. Different surfactant agents were evaluated, and hydrogenated castor oil was selected as the emulsifier agent. The antimicrobial activity of oregano essential oil (Origanum vulgare), thyme essential oil (Thymus vulgaris), and the three formulations were evaluated against Staphylococcus aureus, Streptococcus mutans, Streptococcus salivarius, and Escherichia coli. Results: Pure thyme and oregano essential oils showed higher antimicrobial activity than a 0,2% chlorhexidine solution. The formulations with essential oils plus chlorhexidine and chlorhexidine alone showed antimicrobial activity. The formulation containing only essential oils did not show antimicrobial activity. Conclusions: A canine mouthwash was formulated with chlorhexidine and thyme and oregano essential oil. Based on the evaluation of antimicrobial activity, two of the proposed formulations could be a therapeutic option to reduce the risk and prevent periodontal disease in canines.